Analisis Pengaruh Kepemimpinan Instruksional terhadap Kualitas Kerja Guru di SMK Perguruan Al Washliyah Petumbukan Deli Serdang - Kayamuddin Saragih; Elfrianto Elfrianto; Sri Nurabdiah Pratiwi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
The purpose of this study is to determine the influence of instructional leadership on teacher job quality in the work environment, organizational culture, and work motivation on teacher performance towards job satisfaction at Al Washliyah Petumbukan Vocational School in Deli Serdang. The population in this study is all teachers at Al Washliyah Petumbukan Vocational School, which is 68 people. Due to the population not reaching 100 people, all of them were used as the total sample. The research instrument used was a questionnaire that had been tested for validity and reliability. The results of the study show a positive and significant influence of instructional leadership (X1), achievement motivation (X2), and quality of work life (X3) together on job satisfaction. The magnitude of this influence is indicated by the coefficient of determination R2 (R square) = which means that collectively Job Satisfaction influences teacher performance by 63.0% and the remaining 37.0% is determined by other factors.